PROTOTYPE OF WEB-BASED DAILY WORK REPORT MANAGEMENT SYSTEM USING A DIGITAL PEN - Cheng, John (Journal of Applied Engineering Science, 2019)
As development schemes mature greater and higher complex, it has been more essential to employ information on the means practiced in the organization stage. Nevertheless, the falsities and trial of information oftentimes emerge in the course processing hand-written information. A construction project is performed by a combination of compound entrepreneurs and subcontractors that have diverse technologies and superintendence systems, and constant communication is demanded by yielding the construction information amongst the shareholders. Consequently, this research is to propose the prototype of a web-based periodic record management system that the project shareholders can partake construction information entered employing a digital pen on a web-based system. Based on the submitted system, this subject assumes the outcomes in view of production efficiency, smooth transmission, and resource management. The effect of this investigation provides to enhancing construction fecundity by proposing the web-based daily report management system to construction sites.
Keywords: information technology; Prototyping; construction; management system